Cerdas, Kreatif dan Terampil dalam Pemanfaatan Kain Perca Menjadi Produk Bernilai Jual Guna Mewujudkan Etika Lingkungan di Panti Asuhan Tunas Bangsa Kab. Labuhan Batua Lingkungan di Panti Asuhan Tunas Bangsa Kab. Labuhan Batu - Helena Simangunsong; Juni Atia Intan Sari Sinaga; Maria Margaretha Manik; Melly Andriani Br Ginting; Amin Harahap (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This program aims to empower children at the Tunas Bangsa Orphanage, Labuhanbatu Regency, by teaching creative skills in utilizing scrap fabric into products with sales value. In this activity, scrap fabric which is usually considered as textile waste will be processed into products such as scrunchies, hair bands, and bandanas that can provide economic opportunities for children in the orphanage. In addition, this program also aims to increase environmental awareness by teaching the importance of sustainable textile waste management and environmental ethics. This training is complemented by the values ​​of Citizenship Education (PKN), such as social responsibility and mutual cooperation, which aim to shape the character of children who care about the environment and society. It is hoped that through this program, children can develop creative skills, foster a spirit of social entrepreneurship, and play an active role in preserving the environment. This program also opens up opportunities for them to achieve economic independence and contribute to a broader environmental conservation movement.